Beyond the Classroom Walls: Indonesian EFL Students’ Self-Regulated Learning Experiences in a Flipped Listening Classroom - Destina Kasriyati; Ribut Wahyu Eriyanti; Diah Karmiyati; Nurfaisal Nurfaisal; Puput Arfiandhani; Syahdan Syahdan (IJECA (International Journal of Education and Curriculum Application), 2026)
The rapid advancement of Information and Communication Technology (ICT) has transformed higher education, positioning the Flipped Classroom Model (FCM) as a strategic pedagogical innovation for student-centered learning. This study addresses a significant gap in the literature regarding how students independently regulate their learning within less structured environments, specifically focusing on the "transient" nature of listening skills which demand high levels of concentration and self-regulation. The primary objective of this research is to gain an in-depth understanding of how Indonesian EFL students manage their self-regulated learning (SRL) processes, identifying emerging behaviors and challenges beyond the classroom walls. Employing a qualitative descriptive design, the study utilized semi-structured interviews with 13 undergraduate English Education students at a private university in Indonesia who were selected through purposive sampling. Data were analyzed using Braun and Clarke’s thematic analysis framework. The findings unveil a critical theoretical shift from traditional individualistic self-regulation to "Eco-Systemic SRL Constraints," demonstrating that EFL learners’ metacognitive monitoring and environmental structuring are deeply bounded by their techno-economic realities. While FCL potentially triggers active learner roles, it simultaneously induces "Autonomy Shock" for students transitioning from teacher-dependent cultures. Furthermore, the study identifies that unstable connectivity and un-chunked media deplete students' "Techno-Cognitive Bandwidth," causing infrastructure-related anxiety to override target language processing. The implications suggest that while FCL supports SRL development, successful implementation requires robust institutional digital infrastructure and explicit instructor-led training in goal setting and time management to prevent learner frustration and ensure pedagogical effectiveness.